DIGITIZATION AS A TOOL FOR THE PRESERVATION OF INTANGIBLE CULTURAL HERITAGE OF UNESCO IN UKRAINE IN THE CONDITIONS OF POST-WAR RECONSTRUCTION (Development Service Industry Management, 2023)
The article examines the theoretical, methodological and practical foundations of the transfer of intangible cultural heritage of Ukraine. Thanks to which the historical and cultural peculiarity of our state is preserved.The intangible cultural heritage of Ukraine, due to the full-scale invasion of Russia on the territory of Ukraine, has suffered great losses and is on the verge of losing an important part of the intangible heritage. The work examines the varieties and specifics of the transfer of the intangible cultural heritage of Ukraine. Also, based on research, the work proposes a method of preserving and passing on intangible cultural heritage to our descendants thanks to digitalization.Ukraine, rich in history, traditions and cultural heritage, has many objects of intangible cultural heritage that reflect the richness of the national identity. Intangible cultural heritage includes language, traditions, crafts, folklore, music, dances, religious ceremonies and many other elements that are passed down from generation to generation and form the basis of the country's cultural life.These objects of intangible cultural heritage not only embody valuable knowledge and skills, but are also an important component of the cultural identity of the Ukrainian people. They are embodied in the life of local communities, create a special atmosphere and attract the attention of tourists from all over the world who want to learn about the history and culture of Ukraine.Objects of the intangible cultural heritage of Ukraine have become not only witnesses of past eras and generations, but also living symbols of national self-determination and diversity of cultural expressions. They are a valuable source of knowledge and understanding of Ukrainian history, traditions and values.In this context, it is important to consider objects of intangible cultural heritage as a powerful resource for the development of the tourism industry of Ukraine. They can become central elements of tourist routes, cultural festivals and events that attract the attention of tourists from different countries of the world. The use of objects of intangible cultural heritage in the tourism industry of Ukraine will not only contribute to the preservation of traditions and cultural heritage, but also contribute to economic growth, development of regions and enrichment of the tourist experience of all who visit this magical country.Preservation and promotion of intangible cultural heritage sites in Ukraine is an important task for all stakeholders, including the government, non-governmental organizations and local communities. Thanks to the right approach to the development of tourism, the preservation of traditions and the promotion of interaction between the cultural heritage of different countries, Ukraine can become not only an attractive tourist destination, but also a center of cultural exchange and cooperation.In general, the intangible cultural heritage of Ukraine has great potential for the development of tourism, attraction of tourists, preservation of cultural heritage and promotion of national identity. It creates a unique opportunity for tourists to learn about the history, traditions and culture of Ukraine, and also contributes to the economic development and support of regional communities. The use of this potential requires a systematic approach, cooperation and investment in order to preserve and promote objects of intangible cultural heritage in the tourism industry of Ukraine.The intangible cultural heritage of Ukraine needs special attention and preservation especially in wartime. After all, after its completion, it can become one of the factors of recovery of the economy of Ukraine.
Keywords: intangible heritage; cultural heritage; digitalization; military conflicts